Temper embrittlement of supermartensitic stainless steel and non-destructive inspection by magnetic Barkhausen noise. (June 2019) - Tavares, S.S.M.; Noris, L.F.; Pardal, J.M.; da Silva, M.R.
Abstract: Supermartensitic is a new class of stainless steels used as seamless pipes and forged parts in the oil and gas off shore production. The final mechanical properties of the steel are adjusted by quenching and tempering heat treatments. In this work, a Ti alloyed supermartensitic stainless steel was quenched and tempered at 500 °C, 570 °C, 620 °C and 640 °C. Specimens tempered at 500 °C showed very low toughness and brittle fracture in low temperature Charpy tests. This temper embrittlement effect was detected by magnetic Barkhausen noise (MBN) inspection. Specimens tempered at 620 °C and 640 °C were cooled in water or in furnace after tempering, and those slowly cooled had lower toughness and higher austenite volume fraction. In this case, MBN could not detect the embrittlement effect, probably due to the high austenite (paramagnetic phase) content. Highlights: Temper embrittlement of Ti alloyed supermartensitic steel is associated to secondary hardening due to TiC precipitation. Tempering at 500 °C causes decrease of low temperature toughness. Magnetic Barkhausen Noise detected the temper embrittlement when austenite was not present. Austenite decreases the Magnetic Barkahausen Noise effect.